Outcome of Corneal Collagen Crosslinking for Progressive Keratoconus in Paediatric Patients. (11th June 2014) - Viswanathan, Deepa; Kumar, Nikhil L.; Males, John J.
Abstract : Purpose . To evaluate the efficacy of corneal collagen crosslinking for progressive keratoconus in paediatric patients. Methods . This prospective study included 25 eyes of 18 patients (aged 18 years or younger) who underwent collagen crosslinking performed using riboflavin and ultraviolet-A irradiation (370 nm, 3 mW/cm 2, 30 min). Results . The mean patient age was 14.3 ± 2.4 years (range 8–17) and mean followup duration was 20.1 ± 14.25 months (range 6–48). Crosslinked eyes demonstrated a significant reduction of keratometry values. The mean baseline simulated keratometry values were 46.34 dioptres (D) in the flattest meridian and 50.06 D in the steepest meridian. At 20 months after crosslinking, the values were 45.67 D (P = 0.03 ) and 49.34 D (P = 0.005 ), respectively. The best spectacle corrected visual acuity (BSCVA) and topometric astigmatism improved after crosslinking. Mean logarithm of the minimum angle of resolution (logMAR) BSCVA decreased from 0.24 to 0.21 (P = 0.89 ) and topometric astigmatism reduced from mean 3.50 D to 3.25 D (P = 0.51 ). Conclusions . Collagen crosslinking using riboflavin and ultraviolet-A is an effective treatment option for progressive keratoconus in paediatric patients. Crosslinking stabilises the condition and, thus, reduces the need for corneal grafting in these young patients.